A Comparative Performance Analysis of Conventional Banking and Islamic Banking in Bangladesh - Johora, Fatema - Tuz - (Asian Accounting and Auditing Advancement, 2015)
Commercial banks can be said to be the major contributor to the financial market mechanism in Bangladesh. Two forms of commercial banking systems are functioning here: the conventional banking system and the Islamic banking system. The two banking systems differentiate each other according to their compliance with different norms, values, beliefs, and religious views while conducting business. Conventional banks follow borrowing and lending mechanisms while Islamic banks follow trading and investment mechanisms. Conventional banks provide and receive interest while receiving deposits and providing loans respectively. However, Islamic banks neither pay nor accept interest since it is prohibited in Islam. Rather they do business on the profit and loss sharing concept. The purpose of this experiential study is to compare the performance of both the banking streams and to discover the superiority of any one or at least to find out which one is performing better than the other in which area(s). For the intended performance comparison, all the public limited conventional commercial banks and all the (except one) Islamic commercial banks have been included in the calculation of financial ratios for the years 2007 to 2011. The researcher has calculated six profitability ratios including Return on Equity (ROE), Return on Assets (ROA), Net Interest Margin (NIM), Cost to Income Ratio (COINR), Net Profit Margin (NPM), and Earning Per Shares (EPS); four liquidity ratios containing Liquid Assets to Customer Deposits & Short Term Funds Ratio (LdCDSF), Loans to Deposits (LTD), Loans to Deposits & Borrowing (LTD&B) and Loans to Assets (LTA); four credit risk ratios comprising Capital to Assets Ratio, Common Equity to Assets Ratio (EQTA), Total Equity to Loan Ratio (EQL) and Non-Performing Loans to Loans (NPL). In addition to ratio calculation, the solvency of both the banking streams has also been calculated using a model called Bank-o-meter. The analysis concludes that conventional banks are dominating in profitability and liquidity whereas Islamic banks are leading in credit risk management and solvency maintenance.